Black Panther : the junior novel - McCann, Jim, 1974- (Little, Brown and Co., 2018)
"T'Challa, as the Black Panther and warrior King of Wakanda, must team up with elite members of the Dora Milaje--Wakanda's special forces--and C.I.A. agent Everett K. Ross to defend his kingdom"--Publisher provided.